Empowering Housewives In Initial Handling Of Choking And Fever Seizures In Children In Ko'mara Village, Takalar Regency - Samsir Samsir; Alamsyah Alamsyah; Asri Tuhuri (Universitas AMIKOM Yogyakarta, 2026)
Toddlers are highly vulnerable to emergencies in the home environment, with choking and febrile seizures being the most life-threatening incidents requiring intervention within minutes. Housewives, as primary caregivers, are often the first responders in these situations; however, their knowledge and skills in initial response are still relatively low. This community service project aims to empower housewives in Ko'mara Village, Takalar Regency, through education and hands-on simulation training. The activity was carried out on January 12–17, 2026, involving 15 housewives with toddlers. The methods used included interactive lectures using visual media, demonstrations, and live redemonstrations using infant and child mannequins for choking and febrile seizure management techniques. Pre- and post-activity evaluations showed significant improvements: the average knowledge score increased from 45 to 88 out of 100. Practical skill achievement reached 87% for the Back Blow technique, 80% for the Heimlich Maneuver, and 100% for the recovery position and temperature measurement. These findings demonstrate that a structured short course combining participatory education and simulation-based training is an effective strategy for improving emergency response competency among housewives in communities with limited resources